Identificação de espécies de Cladosporium e a reação de cultivares de nogueira-pecã - Walker, Clair (2016)
The culture of pecan [Carya illinoinensis (Wangenh.) K. Koch] has presented greater economic importance in southern Brazil in recent decades, thus increasing the planted area, mainly in the states of Rio Grande do Sul (RS), Santa Catarina (SC) and Paraná (PR). However, despite the increasing growth of planted area, little research related to diseases in culture and breeding aimed at obtaining cultivars resistant to diseases, have been held in the country. The occurrence of leaf spot symptoms caused by Cladosporium spp. was observed in field in three southern states of Brazil. Given this observation, the general objective of this study was to evaluate the morphological and molecular variability of Cladosporium spp. isolates associated with leaf spot in pecan, checking its distribution in southern Brazil, as well as selecting resistant cultivars as a way to control the disease. The specific objectives were established as follows: a) To identify the species of Cladosporium spp. causing leaf spot in pecan orchards coming from producing areas of the three southern states of Brazil; b) To verify the diversity and morphological and genetic variability, by sequencing elongation factor (TEF - 1α) region, isolates of Cladosporium spp. from pecan plants with symptoms of leaf spot; c) To select efficient morphological characters for separation of isolated groups according to the species to which they belong; d) To confirm the pathogenicity of Cladosporium spp., as well as quantify the incidence and severity of leaf spot in Shawnee‟ and Barton‟ cultivars. For this, leaf samples were taken in 16 symptomatic pecan orchards to the isolation of the pathogen in the states of Paraná, Santa Catarina and Rio Grande do Sul. The isolates were characterized morphologically using mycelial growth, sporulation, colonies pigmentation, conidia and ramoconidia dimensions. These variables were used in the UPGMA analysis in which the isolates were grouped in a dendrogram according to genetic similarity and established characters that contributed most to the divergence. The analysis of 40 isolates by means of morphological and genetic analysis, sequencing of genes from the elongation factor TEF-1α confirmed that the species C. cladosporioides (21 isolates), C. pseudocladosporioides (18 isolates) and C. subuliforme (only one isolate) associated with leaf spot. The region of the elongation factor (TEF-1α) is efficient to identify and group the species associated with pecan included in the C. cladosporioides complex and sporulation is an important morphological characteristic to differentiate the species of Cladosporium spp. All 40 isolates were pathogenic to cultivars Barton‟ and Shawnee‟. The two cultivars were considered susceptible to leaf spot for the three species of Cladosporium spp. tested and there is susceptibility difference for C. pseudocladosporioides, where 'Shawnee' showed greater severity of disease in relation to 'Barton'.